Preliminary toxicity analysis of intraperitoneal carboplatin in combination with intravenous paclitaxel chemotherapy for patients with carcinoma of the ovary, peritoneum, or fallopian tube. Issue 3 (1st April 2005) - Fujiwara, K.; Suzuki, S.; Ishikawa, H.; Oda, T.; Aotani, E.; Kohno, I.
Abstract : The objective of this study was to provide preliminary toxicity data of multiple-cycle combination chemotherapy with intraperitoneal (IP) carboplatin and intravenous (IV) paclitaxel for further clinical trials. The toxicity data of 42 patients with müllerian carcinoma who underwent IP carboplatin therapy in combination with IV paclitaxel were retrospectively analyzed. Chemotherapy was repeated through the Bard IP port placed at initial surgery using IV paclitaxel at 175 mg/m 2 followed by IP carboplatin. The doses of carboplatin were either at area under the curve (AUC) = 5, 6, 6.5, 7, or 7.5. The toxicity data in a total of 237 cycles were analyzed. The median number of cycles for IP chemotherapy was 6 (range: 3–12). The incidences of maximal grade toxicities in all cycles were: grade (G)2/3 nausea/vomiting, 23.8%; G2/3 constipation, 42.9%; G2 abdominal pain, 28.6%; G2/3 sensory neuropathy, 14.3%; motor neuropathy, 4.8%; myalgia/arthralgia 33.4%; G3/4 neutrocytopenia, 85.4%; and G3/4 anemia, 35.4%. These were not related to the dose of carboplatin. The incidences of G3 thrombocytopenia in relation to the dose of carboplatin were AUC = 5, 0%; 6, 31.6%; 6.5, 44.4%; 7, 25.0%; and 7.5, 80%. G4 thrombocytopenia did not occur. A dose of carboplatin between AUC = 6 and 7 with IV paclitaxel at 175 mg/m 2 is warranted for further evaluation.